Realizing Reduced Imperfections via Quantum Dots Interdiffusion in High Efficiency Perovskite Solar Cells. Issue 40 (28th August 2020) - Xie, Lin; Vashishtha, Parth; Koh, Teck Ming; Harikesh, Padinhare Cholakkal; Jamaludin, Nur Fadilah; Bruno, Annalisa; Hooper, Thomas J. N.; Li, Jia; Ng, Yan Fong; Mhaisalkar, Subodh G; Mathews, Nripan
Abstract: Realization of reduced ionic (cationic and anionic) defects at the surface and grain boundaries (GBs) of perovskite films is vital to boost the power conversion efficiency of organic–inorganic halide perovskite (OIHP) solar cells. Although numerous strategies have been developed, effective passivation still remains a great challenge due to the complexity and diversity of these defects. Herein, a solid‐state interdiffusion process using multi‐cation hybrid halide perovskite quantum dots (QDs) is introduced as a strategy to heal the ionic defects at the surface and GBs. It is found that the solid‐state interdiffusion process leads to a reduction in OIHP shallow defects. In addition, Cs + distribution in QDs greatly influences the effectiveness of ionic defect passivation with significant enhancement to all photovoltaic performance characteristics observed on treating the solar cells with Cs0.05 (MA0.17 FA0.83 )0.95 PbBr3 (abbreviated as QDs‐Cs5). This enables power conversion efficiency (PCE) exceeding 21% to be achieved with more than 90% of its initial PCE retained on exposure to continuous illumination of more than 550 h. Abstract : Introduction of multi‐cation hybrid halide perovskite quantum dots reduces ionic defects at the surface and grain boundaries via a solid‐state interdiffusion process. The enhanced moisture and photostability enable power conversion efficiency (PCE) exceeding 21% to be achieved with more than 90% of its initial PCE retained on exposure to continuous illumination of more than 550 h.